Escenarios problematizadores de las organizaciones educativas desde la perspectiva del desarrollo de competencias emocionales en los docentes en formación - Olga Cleosilda Chica-Palma; Jorge Oswaldo Sánchez-Buitrago (Universidad del Magdalena, 2015)
As part of the research entitled "Educational Intitutions conceived as scenarios for the development of emotional competences: a comprehensive reading based on the training of teachers in Escuelas Normales Superiores from Colombia," four comprehensive scenarios were configured which unveil compromising issues of the educational organizations, in relation to emotional training. Four key troublesome scenarios are supported in the present paper, namely, the first one, the new structure and familiar condition that does not provide the necessary emotional models for a qualified integral training; the second one, the emergency boosted from a new human condition that is requiring new answers regarding to the teacher-training organizations; the third one, the new realities and challenges imposed by both society and mass media over the emotional training, and the fourth one, the difficulties and challenges within teaching training, particularly connected with emotions. All the above, is aimed to support the systematic incorporation of the emotional competences development within the formative proposals of teachers; intended to contribute to an educational quality improvement and especially enhance the conditions and possibilities of the teaching profession execution.